The role of regulatory T cells and genes involved in their differentiation in pathogenesis of selected inflammatory and neoplastic skin diseases. Part III: Polymorphisms of genes involved in Tregs’ activation and function - Nedoszytko, Bogusław; Sokołowska-Wojdyło, Małgorzata; Renke, Joanna; Lange, Magdalena; Trzonkowski, Piotr; Sobjanek, Michał; Szczerkowska-Dobosz, Aneta; Niedoszytko, Marek; Górska, Aleksandra; Romantowski, Jan; Skokowski, Jarosław; Kalinowski, Leszek; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Regulatory T cells (Tregs) represent a cell type that promotes immune tolerance to autologous components and maintains immune system homeostasis. The abnormal function of Tregs is relevant to the pathogenesis of several skin diseases like psoriasis, atopic dermatitis, systemic lupus erythematosus, cutaneous T-cell lymphomas, and skin cancer and is also important in rheumatoid arthritis, diabetes and other autoimmune diseases. In this review, we will summarize the role of mutations and/or polymorphisms of genes involved in Tregs development, and functions in the pathogenesis of selected skin diseases.